Difficulties experienced by nursing professionals in the preparation of medicine - Cícera Maria Braz da Silva; Leonardo José Dantas Pinheiro de Araújo; Edilma de Oliveira Costa; Maria Isabel da Conceição Dias Fernandes; Ana Luisa Brandão de Carvalho Lira; Ozimar Azevêdo (Rev Rene)
We aimed at analyzing the difficulties experienced by nursing professionals during the preparation of medication. It is a descriptive study conducted in a university hospital in a city in northeastern Brazil. 25 nursing professionals were interviewed, using a semi-structured interview script, during the months of January and February 2013. The difficulties during the preparation of medicine were: prescription barely legible; labels of medicine with small and similar letters; lack of exclusive venue for this activity; wrong expedition by the drugstore; inadequate lighting, and accumulation of functions. The conclusion is that difficulties related to the pharmaceutical process were identified. So, in order to ensure safe medicine therapy, it is necessary to have mandatory strategies which favor the effectiveness of this process.